2013
DOI: 10.1007/s11064-013-0971-x
|View full text |Cite
|
Sign up to set email alerts
|

The Antiretroviral Protease Inhibitor Ritonavir Accelerates Glutathione Export from Cultured Primary Astrocytes

Abstract: Antiretroviral protease inhibitors are a class of important drugs that are used for the treatment of human immunodeficiency virus infections. Among those compounds, ritonavir is applied frequently in combination with other antiretroviral protease inhibitors, as it has been reported to boost their therapeutic efficiency. To test whether ritonavir affects the viability and the glutathione (GSH) metabolism of brain cells, we have exposed primary astrocyte cultures to this protease inhibitor. Application of ritona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 54 publications
3
12
0
Order By: Relevance
“…Recently a number of compounds have been reported to strongly stimulate rapid GSH export from viable astrocytes, including formaldehyde [96], arsenate and arsenite [97,98] and antiretroviral protease inhibitors [99,100]. Although all of these stimulated GSH export processes were almost completely prevented by inhibition of Mrp1, the molecular mechanism how such structurally very diverse compounds accelerate Mrp1-mediated GSH export remains unclear.…”
Section: Gsh Redox Cyclingmentioning
confidence: 99%
“…Recently a number of compounds have been reported to strongly stimulate rapid GSH export from viable astrocytes, including formaldehyde [96], arsenate and arsenite [97,98] and antiretroviral protease inhibitors [99,100]. Although all of these stimulated GSH export processes were almost completely prevented by inhibition of Mrp1, the molecular mechanism how such structurally very diverse compounds accelerate Mrp1-mediated GSH export remains unclear.…”
Section: Gsh Redox Cyclingmentioning
confidence: 99%
“…GSH is an important antioxidant in the brain that participates in interactions between astrocytes and neurons [ 20 22 ]. Previous studies have shown that GSH is synthesized and released by astrocytes and can then be used by neurons to resist oxidative stress [ 21 , 23 ]. In addition, elevated DJ-1 expression increases GSH levels in co-cultures of astrocytes and neurons [ 24 ], but it is not clear how these two molecules interact.…”
Section: Introductionmentioning
confidence: 99%
“…While beneficial in their suppression of HIV, HAART drugs have a multitude of side effects including myopathy, hepatotoxicity, hypersensitivity reactions, lipodystrophy, and insulin resistance ( Feeney and Mallon, 2010 ). In vitro , there has been evidence of HAART drugs inducing ER stress ( Sato et al, 2012 ), unfolded protein response ( Zhou et al, 2005 ), and changes to cellular metabolism ( Arend et al, 2013 ). These side effects suggest that cells may undergo a great deal of stress in response to HAART drugs.…”
Section: Introductionmentioning
confidence: 99%